Exploring the connections between green economy and informal economy in South Africa - Smit, Suzanne (Academy of Science of South Africa, 2018)
The notion of an inclusive green economy in the context of sustainable development and poverty eradication requires an approach that engages with the informal economy. However, the informal economy is generally ignored or undervalued in discussions on the green economy. This paper set out to bolster this argument by identifying the ways in which the green economy and the informal economy may be connected by establishing the extent to which policies and plans relating to green economy connect with the informal economy, and recognising several informal green activities. The barriers and opportunities for connecting the two spheres were also explored as well as possible ways in which such activities may be supported at different levels of organisation. In the case of South Africa, many informal green activities that contribute to sustainable livelihoods are recognised. However, issues pertaining to procedure, process and participation hinder the transition to a truly inclusive green economy.